Sharing Stories of Mothering, Academia and the COVID 19 Pandemic: Multiple Roles, Messiness and Family Wellbeing - Croxen, Hanneke; Jackson, Margot; Asirifi, Mary; Symonds-Brown, Holly (INYI Journal, 2022)
The Coronavirus (COVID-19) pandemic has caused disruption. Responsibilities increased especially for people who identify as mothers needing to balance work and caring for their child(ren). Through the use of personal narratives, we explored our experiences as mothers who work in academia. The purpose of this commentary is to explore the commonalities of our experiences of trying to maintain the multiple roles and responsibilities demanded from us as mothers and academics during the COVID-19 pandemic. Two themes emerged: multiple roles and responsibilities and embracing the ‘messiness’. The need to take on multiple roles simultaneously such as working from home and parenting was challenging. Embracing the ‘messiness’ demonstrated that caring for our children while working from home caused their needs and our time to focus on them to be compromised. Our work and productivity were impacted with minimal available support but this was not acknowledged within the business as usual practices of the university. The conditions that negatively impact us, also negatively impact our children. Children have needed to adjust to pandemic conditions and their support has been compromised due to the other competing demands mothers face. As academics, our future work will be informed and shaped from this experience, and so too will the growth and development of our children. Our experiences from this pandemic highlight the gendered inequities present within academia and the potential negative effects on child well-being. We call attention to this issue to help promote change and advocate for mothers working in academia and elsewhere.